ISLAMIC EDUCATION LEARNING STRATEGIES BASED ON MULTIPLE INTELLIGENCES IN ISLAMIC SCHOOL - Firman Mansir; Halim Purnomo (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2020)
The objective of this study was to explore and find out the Islamic education learning (PAI) method which is suitable with the dynamics of the students to make them easier in understanding the subject and improve their achievement using multiple intelligences. This study was Classroom Action Research. Classroom Action Research involved the teacher’s attempt (the researcher) in the form of the learning process. Validity concept and instrument reliability used in the data collection. In this research also known as practical validity/reliability, which means that as long as the members of the action research group decide that the instrument is valid and reliable, it can be used. Islamic education learning strategies need to use intelligence by solving the problems faced by the students, developed new problems to be solved, and make something useful in their life. Therefore, multiple intelligences in Islamic education learning is part of an effective strategy to facilitate the subject and improve student achievement.